Communications and Networking An Introduction - Cowley, John.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Computer communications and networks are an integral part of any computer science degree, with the technology growing ever more pervasive in modern life. This clear and easy-to-follow textbook presents a detailed introduction to the essentials of networking and communications technologies, supported by numerous diagrams, examples and exercises designed to increase confidence in using and understanding communications systems. Thoroughly revised and updated, this much-anticipated new edition retains the popular step-by-step approach of the original, organised to help those without a strong knowledge of the subject matter to grasp the material quickly. Topics and features: Provides chapter-ending summaries and review questions, an Appendix on TCP/IP packet formats and an expanded Glossary Supplies supplementary material at the associated Springer website, including teaching slides, solutions to the end-of-chapter questions and supplementary exercises with solutions Presents a greater emphasis on mobile computing and network security, and extended coverage of IPv6 (NEW) Discusses networking models and standards, local area and wide area networks, network protocols, TCP/IP-based networks, network management and wireless communications Examines grid and cloud computing, microblogging, mobile ad hoc networks, near-field communication, Power over Ethernet and the Ground Positioning System (NEW) Written specifically for undergraduate students of computing with no previous experience in the field, this comprehensive and authoritative textbook draws upon the author$1 (Bs many years of teaching experience.s
Introduction -- Communications Technologies -- Networking Models and Standards -- Local Area Networks -- Wide Area Networks -- Network Protocols -- Internet Application Layer Protocols -- Network Security -- Network Management -- Wireless Networks.
Keywords: Computer science; Computer network architectures; Computer Science; Computer Systems Organization and Communication Networks